2005
DOI: 10.1007/s00216-005-0177-4
|View full text |Cite
|
Sign up to set email alerts
|

Double-layer Tedlar bags: a means to limit humidity evolution of air samples and to dry humid air samples

Abstract: Tedlar bags, which are widely used to collect air samples, especially VOCs and odorous atmospheres, can allow humidity to diffuse when relative humidity levels differ between the inside and outside. Starting with dry air inside the bag and humid air outside, we monitored equilibrium times under several conditions showing the evolution and influence of collected volumes and exposed surfaces. A double-film Tedlar bag was made, to limit the impact of external humidity on a sample at low humidity level. With the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…In contrast, the CO mole fractions decrease in the Tedlar bags, coupled with a significant increase of water vapour mole fractions of up to ~1% (Fig. 2d), which is due to the high permeability of the bag material to water vapour and has been observed in previous studies (Beghi and Guillot, 2006;Cariou and Guillot, 2006). The increase of water vapour mole fractions in the MLF bags is only up to 0.01%.…”
Section: The Storage Test Results 20supporting
confidence: 61%
See 1 more Smart Citation
“…In contrast, the CO mole fractions decrease in the Tedlar bags, coupled with a significant increase of water vapour mole fractions of up to ~1% (Fig. 2d), which is due to the high permeability of the bag material to water vapour and has been observed in previous studies (Beghi and Guillot, 2006;Cariou and Guillot, 2006). The increase of water vapour mole fractions in the MLF bags is only up to 0.01%.…”
Section: The Storage Test Results 20supporting
confidence: 61%
“…Previous studies show that the material of Tedlar bags is prone to water vapour diffusion (Beghi and Guillot, 2006;Cariou and Guillot, 2006), which leads to humidified air samples after four hours of storage. The CO2, CH4 and CO dry mole fractions are obtained by applying the water vapour corrections described in Chen et al, 2013 andRella et al, 2013. …”
Section: Where [X] Is the Measured Mole Fraction 15mentioning
confidence: 99%
“…However, Nielsen and Jonsson [34] did not observe losses for H 2 S, MeSH, COS, DMS and CS 2 in samples with RH = 30% stored in Tedlar bags over the period of 20 h. The main problems during such studies are instability of water concentration in some sampling containers (e.g. Tedlar [27,28,34]) and some analytical problems during the gas chromatographic analysis of VSCs in humidified samples. The most commonly reported humidity effects are: decrease of the adsorption capacity of the sorbents, plugging of cold traps at sub-zero temperatures and retention time variations in the case of the sorbent trapping [21,38,39], and decrease of the extraction efficiency in the SPME [35].…”
Section: Stability Testsmentioning
confidence: 91%
“…This is due to their moderate price, inertness, relatively good durability and reusability. Unfortunately, several phenomena affecting sample composition like permeation through the bag walls, reversible/irreversible adsorption and pollutants emission from bags film have been reported [24,[27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Tedlar bags may be effective at holding VSCs in dry environments (Sulyok et al, 2001); however, in humid environments, this technique has been shown to sorb and potentially degrade VSCs (Kuster and Goldan, 1987). Drying of air using desiccates has been shown to improve results with Tedlar bags, but the results are short term due to the diffusion of humidity into the bags with storage (Nielsen and Jonsson, 2002a, b;Cariou and Guillot, 2006). Stainless-steel canisters and surfaces have also been found unsuitable material for the sampling and transferring of VSCs since exposure to these surfaces leads to the rapid loss of the most reactive compounds (Parmar et al, 1996;Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%